(untitled) (GIST – Education and Learning Research Journal, 2009)
This paper shares the results of a study on the benefits which an experiential education program has on students in the K-12 range. The study was carried out at a bilingual North American-style college preparatory school located in Colombia, South America. Research was based on experiences obtained through the coordination and implementation of an experiential education program during the 2008-09 school year. The findings deal with experiential education as a pedagogical philosophy.